Humic and Fulvic Acids of Gliricidia and Tithonia Composts for Aluminium Detoxification in an Ultisol - Wahyudi, Imam; Handayanto, Eko; Sykehfani, Sykehfani; Utomo, Wani Hadi (Faculty of Agriculture University of Brawijaya and Indonesian Agronomic Assossiation, 2010)
A laboratory experiment was conducted to elucidate roles of Gliricidia sepium and Tithonia diversifolia composts and their extracted humic and fulvic acids on aluminum concentration in an Ultisol. Those composts and humic and fulvic acids extracted from them mixed with soil were arranged in a complete randomized design with three replicates, and incubated for 90 days. Al concentration and pH of the soil were measured at 0, 3, 10, 20, 30, 45, 60, 75 and 90 days after incubation. Results of the study showed that the highest decrease in exchangeable Al concentration (90.5%) was observed for Tithonia fulvic acid treatment during 90 days, followed by Tithonia compost (88.4%), Gliricidia fulvic acid (82.3%), Gliricida compost (82.2%), Tithonia humic acid (75.66%), and Gliricidia humic acid (73.46%) treatments, whereas control only decreased exchangeable Al concentration by 0.9%. The rate of change in exchangeable Al concentration was fast for the first 45 days, but it then slowed down for the second 45 days (45-90 days). This was particularly observed with organic acid treatments, whereas compost treatment still showed a subsequent decrease. Patterns of Al chelate and pH were very similar to that of exchangeable Al. It was thus concluded that roles of humic and fulvic acids in reducing exchangeable Al was only short term, whereas compost played roles in the long term.Keywords: Ultisol, aluminium, humic acid, fulvic acid, gliricidia sepium, tithonia diversifolia